Enhancing cognitive function through blood flow restriction: An effective resistance exercise modality for middle-aged women - Dohyeon Lee; Kyeongho Byun; Sewon Lee (Journal of Exercise Science & Fitness)
Purpose: Cognitive decline progresses more rapidly in women than in men, with a higher prevalence of neurodegenerative diseases observed in females. Exercise has been shown to enhance cognitive function through the upregulation of neurotrophic factors such as brain-derived neurotrophic factor (BDNF), vascular endothelial growth factor (VEGF) and insulin-like growth factor-1 (IGF-1). However, high-load resistance exercise may not be suitable for all populations, particularly middle-aged women. Low-load resistance exercise with blood flow restriction (LLBFR) has emerged as an effective alternative. This study investigated the acute effects of LLBFR on neurotrophic factors and cognitive function in middle-aged women. Methods: Fifteen healthy middle-aged women completed a randomized crossover trial involving four conditions: control (CON), low-load resistance exercise (LLRE), LLBFR, and moderate-load resistance exercise (MLRE). Cognitive function was assessed before and after each session using the color-word matching Stroop task (CWST). Blood samples were analyzed for serum levels of BDNF, VEGF, and IGF-1, and lactate concentrations were measured to evaluate metabolic responses. Results: Only the LLBFR condition showed significant improvements in CWST reaction time (p = 0.002) with no changes in error rates, indicating enhanced cognitive performance. Serum BDNF and VEGF levels increased significantly following both LLBFR (p < 0.001, p = 0.014, respectively) and MLRE (p < 0.001, p = 0.004, respectively), whereas IGF-1 levels remained unchanged across conditions. Increases in lactate concentrations were positively correlated with changes in BDNF and VEGF (p < 0.001 for both), but not with IGF-1. Conclusion: A single session of LLBFR improved cognitive function and upregulated neurotrophic factors, particularly BDNF and VEGF, in middle-aged women. These findings suggest that LLBFR may be an effective intervention for promoting cognitive health in this population.